2021
DOI: 10.1111/jpn.13658
|View full text |Cite
|
Sign up to set email alerts
|

Dietary mulberry‐leaf flavonoids supplementation improves liver lipid metabolism and ovarian function of aged breeder hens

Abstract: Mulberry‐leaf flavonoids (MF), extracted from mulberry leaves, exert antioxidant and hypolipidemic effects. The purpose of this experimental study was to investigate the effects of dietary MF on the ovarian function and liver lipid metabolism of aged breeder hens. We used 270 (60‐weeks‐old) Qiling breeder hens randomly assigned in 3 treatments with supplemental dietary MF doses (0, 30, 60 mg/kg). The results showed that dietary MF significantly improved the egg‐laying rate, followed by the reduced feed convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…In this study, it was found that the replacement of maize silage with mulberry silage in diet significantly increased the EE content in longissimus dorsi muscles of Hu lambs. Studies have shown that the flavonoids rich in mulberry leaves have a regulatory effect on animal fat deposition and lipid metabolism [ 46 ], which might be the reason for the increase in the EE content after maize silage was replaced by mulberry silage in this experiment. Studies have shown that the final pH value of mutton after slaughter should be between 5.6 and 6.4 [ 47 ].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, it was found that the replacement of maize silage with mulberry silage in diet significantly increased the EE content in longissimus dorsi muscles of Hu lambs. Studies have shown that the flavonoids rich in mulberry leaves have a regulatory effect on animal fat deposition and lipid metabolism [ 46 ], which might be the reason for the increase in the EE content after maize silage was replaced by mulberry silage in this experiment. Studies have shown that the final pH value of mutton after slaughter should be between 5.6 and 6.4 [ 47 ].…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that plants and plant extracts can be used as feed additives to improve egg production performance, egg quality and immunity of chickens, and to reduce cholesterol levels (7). As everyone knows, plants are rich in many natural bioactive compounds, such as flavonoids and polysaccharides, among which mulberry leaf flavonoids can improve egg production and antioxidant capacity of chickens and improve feed conversion ratio (8).…”
Section: Introductionmentioning
confidence: 99%
“…Egg yolk formation, which is closely correlated with molecular and physiological characteristics of the liver, constitutes an essential process of egg production in hens ( Zhu et al, 2020 ). At the late laying stage of the hen, egg production decline is accompanied by excessive lipid deposition ( Wang et al, 2020a ), reductions in yolk precursor formation ability ( Huang et al, 2022 ) and decreased in liver antioxidant capacity ( Qi et al, 2019 ). It is demonstrated that dietary supplemented with plant derived extracts could improve egg production via regulating lipid metabolism, increasing yolk formation, attenuating hepatic oxidative stress, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to commercial hens, the laying performance of broiler breeder hens decreased dramatically during the late laying period, which reduce the economic benefits of broiler breeder hens seriously ( Zhang et al, 2019 ; Chen et al, 2021 ). Previous studies demonstrated that the egg laying rate declines sharply during the late laying period of hens might relate to changes in serum reproductive hormones ( Hao et al, 2021 ), ovarian dysfunction ( May-Panloup et al, 2016 ), reduction in numbers of hierarchical follicles ( Yao et al, 2022 ) and liver function failure ( Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%